The genome sequence of the Violet Copper, Lycaena helle (Denis & Schiffermüller, 1775) [version 1; peer review: 2 approved] - Manel Niell; Tyler S. Alioto; Roger Vila; Benjamin Komac; Vanesa Arroyo; Marta Gut; Fernando Cruz; Jèssica Gómez-Garrido; Silvia Carbonell; Francisco Cámara; Roger Caritg; Clara Pladevall; et al. (F1000Research)
We present a genome assembly from an individual female Lycaena helle (the Violet Copper; Arthropoda; Insecta; Lepidoptera; Lycaenidae). The genome sequence is 547.31 megabases in span. The entirety of the genome sequence was assembled into 25 contiguous chromosomal pseudomolecules with no gaps, including the Z and W sex chromosomes. The mitochondrial genome has also been assembled and is 15.5 kilobases in length. Gene annotation of this assembly identified 20,122 protein coding genes.